Strong gravitational lensing and shadow constraint from M87*of slowly rotating Kerr-like black hole - Kuang, Xiao-Mei; Övgün, Ali (Academic Press Inc Elsevier Science, 2022)
Motivated by (i) more and more interest in strong gravitational lensing by supermassive black holes due to the achievement of EHT observations, (ii) the ongoing popular topic on the possi-bility of Lorentz symmetry being broken in gravitation and its consequences, we will apply the Einstein bumblebee gravity with Lorentz violation (LV) to the study of strong gravitational lensing effect and the black hole shadow of slowly rotating Kerr-like black hole. In the strong gravitational lensing sector, we first calculate the deflection angle; then treating the slowly rotating Kerr-like black hole as supermassive M87* black hole, we eval-uate the gravitational lensing observables (position, separation and magnification) and the time delays between the relativistic images. In the black hole shadow sector, we show the effect of LV parameter on the luminosity of the black hole shadow and photon sphere using the infalling spherical accretion. Moreover, we explore the dependence of various shadow observables on the LV parameter, and then give the possible constraint on the LV parameter by M87* black hole of EHT observations. We find that the LV parameter shows significant effect on the strong gravitational lensing effect, the black hole shadow and photon sphere luminosity by accretion material. Our results point out that the future generations of EHT observation may help to distinguish the Einstein bumblebee gravity from GR, and also give a possible constrain on the LV parameter. (c) 2022 Elsevier Inc. All rights reserved.
Keywords: Black hole shadow cast; Strong gravitational lensing; Bumblebee gravity theory